Distribution. Most of Europe, from the British Is and NW France E to W Siberia as far E as Irtysh and Ob rivers, and from S Sweden, S Finland, and S Karelia (Russia) S to N Italy and N Balkans; marginally present also in NW Kazakhstan. In E Europe and in Asia the border roughly follows the extreme extension of the taiga in the N (northernmost record is from Pechora River close to 68°N) and the steppe-forest—steppe transition in the S. Present on some Is in the Baltic Sea and around Denmark (Oland, Funen, Zeeland, Bjgrng, Tasinge, Tung, Langeland, Riigen, Usedom, and Wollin), around Great Britain (Sky, Mull, Anglesey, Wight, and Jersey), offshore W coast of France (Ouessant and Ré), and on Cres (Croatia) as the only Mediterranean I. in Talpidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2018)
Distribution. Most of Europe, from the British Is and NW France E to W Siberia as far E as Irtysh and Ob rivers, and from S Sweden, S Finland, and S Karelia (Russia) S to N Italy and N Balkans; marginally present also in NW Kazakhstan. In E Europe and in Asia the border roughly follows the extreme extension of the taiga in the N (northernmost record is from Pechora River close to 68°N) and the steppe-forest—steppe transition in the S. Present on some Is in the Baltic Sea and around Denmark (Oland, Funen, Zeeland, Bjgrng, Tasinge, Tung, Langeland, Riigen, Usedom, and Wollin), around Great Britain (Sky, Mull, Anglesey, Wight, and Jersey), offshore W coast of France (Ouessant and Ré), and on Cres (Croatia) as the only Mediterranean I. Published as part of Russell A. Mittermeier & Don E. Wilson, 2018, Talpidae, pp. 52-619 in Handbook of the Mammals of the World – Volume 8 Insectivores, Sloths and Colugos, Barcelona :Lynx Edicions on page 613, DOI: 10.5281/zenodo.6678191